IMPLEMENTATION OF THE JIBRIL METHOD IN IMPROVING THE QUALITY OF AL-QUR'AN READING - Bahari, Fahmi Dina Maula; Iqna’a, Faiq Julia; Abdullah, Abdullah (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
This study aims to explore the implementation of the Jibril Method in improving the quality of Qur'an reading at the Center for Qur'anic Science Education at the Nurul Jadid Islamic Boarding School. The research method is descriptive and qualitative, collecting data through interviews, observations, and documentation. This study focuses on three main aspects, namely learning planning, learning implementation, and learning evaluation based on the Jibril Method. The study results indicate that learning planning at the Center for Qur'anic Science Education aims to produce students who can read the Qur'an well and fluently and understand tajwid theoretically and practically. In its implementation, the Jibril Method is applied through the talking-taqlid technique with tahqiq and tartar, which is carried out in four stages of learning, starting from Al-Fatihah and Juz Amma to Juz 16-30. Learning evaluation is carried out through routine exams, level promotion exams, and final exams to obtain a certificate of Qur'an sanad. This study concludes that the Jibril Method significantly improves the quality of Qur'an reading with a structured and sustainable approach.